2016
DOI: 10.2105/ajph.2015.302942
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Improving Home Environments on Energy Intake and Physical Activity: A Randomized Controlled Trial

Abstract: The intervention was effective in changing home environments and reducing energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…Studies were published between 1980 and 2017 (five in 1980s, one in 90s and four since 2010) in the USA ( n = 7), Denmark [38], India [39] and Japan [40], with a total of 1320 participants (see Table 1). Seven studies took place within community settings, two took place in the workplace [38, 40] and one home intervention [41]. Six studies reported mean age, ranging from 30 to 59 years [36, 38, 4043].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were published between 1980 and 2017 (five in 1980s, one in 90s and four since 2010) in the USA ( n = 7), Denmark [38], India [39] and Japan [40], with a total of 1320 participants (see Table 1). Seven studies took place within community settings, two took place in the workplace [38, 40] and one home intervention [41]. Six studies reported mean age, ranging from 30 to 59 years [36, 38, 4043].…”
Section: Resultsmentioning
confidence: 99%
“…All but one study [44] reported gender: of the 1214 participants, 1041 (86%) were female. Four studies exclusively recruited women [39, 41, 43, 45], one recruited only men [40]. In terms of commitment device type, eight studies reported the use of behavioural contracts (1.8 BCTTv1), one specified the use of verbal commitments (1.9) by male spouses of female participants in addition to the contracts [43], one described an online/app based pledge [38], and one reported a public commitment to an outcome (rather than a behaviour) [39].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that continued evaluation to identify the combination of MTM strategies that support sustained PA change should be researched. 34…”
Section: Discussionmentioning
confidence: 99%
“…Mechanization of industries, like agriculture, has led to less physical activity among rural men. Poor food quality, excessive calorie consumption, eating while doing other activities, and culturally rooted community characteristics contribute to unhealthy rural diets (Chrisman, Nothwehr, Yang, & Oleson, ; Kegler et al., ). Rural men have chronicled health disparities (e.g., environmental‐structural barriers, lack of preventive services, high obesity prevalence) that serve as public health threats to this hard‐to‐reach population (Meit et al., ).…”
Section: Introductionmentioning
confidence: 99%